100 books for girls to grow on : lively descriptions of the most inspiring books for girls, terrific discussion questions to spark conversation, great ideas for book-inspired activities, crafts, and field trips /: lively descriptions of the most inspiring books for girls, terrific discussion questions to spark conversation, great ideas for book-inspired activities, crafts, and field trips. (©1998) - Unknown
No abstract available